Green human resource management (GHRM) and sustainability: A mini review - Kevser Meric Atakan (Journal of Global Business Insights)
This mini review explores the evolving role of Green Human Resource Management (GHRM) in advancing sustainability within organizational structures. As environmental concerns become increasingly central to global business agendas, organizations are compelled to expand their focus beyond profitability to incorporate ecological responsibility. Within this shift, GHRM emerges as a strategic approach that integrates environmental considerations into core human resource functions. The review synthesizes current literature to evaluate how HR practices such as recruitment, training, performance evaluation, and incentive systems are being adapted to support environmental goals. Evidence from qualitative analyses suggests that organizations are gradually embedding sustainability into their internal culture by prioritizing candidates with ecological awareness, offering sustainability-oriented training modules, and incorporating environmental contributions into performance appraisals. By reframing HR functions through a sustainability lens, GHRM facilitates a deeper organizational alignment with ecological objectives. Furthermore, the study highlights the potential of GHRM to foster long-term behavioral change among employees, encouraging the adoption of environmentally responsible practices across all levels of the organization. This review contributes to the growing discourse on sustainable management by emphasizing the strategic importance of human capital in achieving ecological and economic resilience.